2021
DOI: 10.1111/nicc.12600
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge acquisition and retention among nurses after an educational intervention on endotracheal cuff pressure

Abstract: Background Nurses play a key role in the proper management of endotracheal tube (ETT) cuff pressure, which is important for patients' safety, so it is vital to improve nurses' knowledge on safe cuff management practices. Aims and objectives This study aimed to evaluate the effectiveness of an educational intervention related to ETT cuff pressure management on improving and retaining critical care nurses' knowledge. Design A single group pre‐post interventional study was conducted involving 112 registered nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…This inadequacy might be linked to limited opportunities for ED nurses to partake in relevant training. Hence, structured theoretical courses and practical guidance could assist in enhancing nurses' knowledge of airbag management[ 18 , 19 ]. Furthermore, studies by Higgs et al [ 20 ] demonstrated that adherence to evidence-based guidelines in airbag management can significantly mitigate complications.…”
Section: Discussionmentioning
confidence: 99%
“…This inadequacy might be linked to limited opportunities for ED nurses to partake in relevant training. Hence, structured theoretical courses and practical guidance could assist in enhancing nurses' knowledge of airbag management[ 18 , 19 ]. Furthermore, studies by Higgs et al [ 20 ] demonstrated that adherence to evidence-based guidelines in airbag management can significantly mitigate complications.…”
Section: Discussionmentioning
confidence: 99%
“…Murugiah et al 14 conducted a pre‐ and post‐intervention study to assess the acquisition and retention of knowledge about endotracheal (ETT) cuff pressure among registered nurses in an adult general intensive care unit in Kuala Lumpur. This is an important topic because, although ETT cuff pressure management is a key critical care nursing role, and poor cuff management is associated with life‐threatening complications, 15,16 previous research suggests inadequate knowledge and poor or inconsistent practice 17‐19 .…”
mentioning
confidence: 99%